Stereometric analysis of TiO2 thin films deposited by electron beam ion assisted - Shakoury, Reza; Arman, Ali; Ţălu, Ştefan; Dastan, Davoud; Luna, Carlos; Rezaee, Sahar (Optical and quantum electronics, 2020)
The micromorphology and semiconductor properties of TiO 2 thin films growth using different ion beam energies have been finely analyzed using atomic force microscopy (AFM), ultra-violet visible (UV–visible) spectroscopy and stereometric analysis. The AFM measurements and surface stereometric analysis are essential for the accurate characterization of the 3-D surface topographic features and allow the determination of the 3-D surface texture parameters that influence the optical properties of the material. The samples were divided into four groups to discuss the obtained results, according to the ion beam energy applied in the sample preparation. The results obtained from experimental measurements suggested that the surface of samples prepared at lower beam energy had the most regular surface (Sq = 6.25 nm), while the most irregular surface was found in samples prepared with the highest ion beam energy (Sq = 13.40 nm). The transmittance (%) and reflectance (%) spectra, and the band gap energy experienced noticeable changes with increasing applied energy and deposition pressures due to the increase of the surface tension and decrease of the grain sizes. Our investigation shows that the deposition pressure and applied energy affect the optical and the roughness of titania thin films, which partially contribute to the functionality of the surface that, in turn, makes titania useful for the fabrication of different optoelectronic devices.